2021
DOI: 10.1038/s41598-021-96365-w
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of viable Babesia bovis merozoites to study parasite invasion

Abstract: Babesia parasite invades exclusively red blood cell (RBC) in mammalian host and induces alterations to host cell for survival. Despite the importance of Babesia in livestock industry and emerging cases in humans, their basic biology is hampered by lack of suitable biological tools. In this study, we aimed to develop a synchronization method for Babesia bovis which causes the most pathogenic form of bovine babesiosis. Initially, we used compound 2 (C2), a specific inhibitor of cyclic GMP-dependent protein kinas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 31 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…The knockdown of BbVEAP in the presence of inducer was ~90% at protein level (Figure 3B) [26]. This reduction confirmed the role of BbVEAP in parasite development in the RBC, VESA1 export and cytoadhesion of iRBCs to endothelial cells [26,60]. Riboswitch system could be simply employed by insertion of glmS sequence at 3' non-coding region of the gene of interest open reading frame, downstream of the stop codon and is a promising method to be used for mRNA knockdown of Babesia.…”
Section: Conditional Knockdown Systemssupporting
confidence: 58%
See 1 more Smart Citation
“…The knockdown of BbVEAP in the presence of inducer was ~90% at protein level (Figure 3B) [26]. This reduction confirmed the role of BbVEAP in parasite development in the RBC, VESA1 export and cytoadhesion of iRBCs to endothelial cells [26,60]. Riboswitch system could be simply employed by insertion of glmS sequence at 3' non-coding region of the gene of interest open reading frame, downstream of the stop codon and is a promising method to be used for mRNA knockdown of Babesia.…”
Section: Conditional Knockdown Systemssupporting
confidence: 58%
“…Currently, iRBCs are being used for transfection. Large-scale preparation of parasite merozoites is available and may improve the efficiency of transfection [60].…”
Section: Future Perspectivementioning
confidence: 99%
“…Mammalian RBCs are terminally differentiated and anucleate and lack cellular machinery and metabolism. Babesia parasites have a fast metabolism and require nucleic acids and proteins, and the relatively short doubling time (10 to 12 h for B. bovis) and DNA replication (2.9 h for B. bovis) [65] necessitate uptake of metabolic precursors from the host plasma, such as sugars, purines, and amino acids. For P. falciparum iRBCs, studies using osmotic lysis, patch-clamp methods, and radioactive labeled substrates have documented increases in permeabilities to various nutrients, called the new permeability pathway or plasmodial surface anion channel (PSAC) [70,71].…”
Section: Nutrient Uptakementioning
confidence: 99%
“…Given that BbVEAP knockdown did not affect SBP4 export, BbVEAP expression is necessary for the export and correct localization of a subset of proteins including VESA1 and ridge-forming proteins. Additionally, it was shown that BbVEAP is indispensable for parasite development in the RBC, making it the only known essential exportome protein [ 33 , 65 ]. The existence of VEAP among piroplasma parasites indicates a piroplasma-specific conserved function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation